Hungarian Monitoring, 21 February 1989 . [Magyar rádiófigyelő], 1989. február 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Iranian premier on foreign tour - Trial of dramatist Havel in Czechoslovakia - When can GDR citizens travel to the West after the restrictions? - Soviet foreign minister's Egyptian talks - European Parliament's hearings on the Romanian issue Domestic Affairs: - Central Committee continues its work today: agricultural policy debates, situation of the market economy - Law on assembly in preparation - Hungarian PEN Club presidium expresses concern in a telegram over Czechoslovak Writers' Association judgment of Vaclav Havel - Hungarian Lawyers' Association wishes to offer institutional assistance to MPs in their work Economy: - National Planning Office Council discusses renewal of economic planning - Ministerial council decision means that farms in underdeveloped areas can receive tax allowances to set up workshops Külpolitika: - Az iráni miniszterelnök körútra indult - Havel drámaíró pere Csehszlovákiában - Milyen esetben utazhat az NDK állampolgár Nyugatra a szigorítás után? - A szovjet külügyminiszter egyiptomi tárgyalásai - Az Európa Parlament meghallgatásai Románia ügyében Belpolitika: - Ma folytatta munkáját a KB.: agrárpolitikai vita, piacgazdaság helyzete - A készülő gyülekezési törvény - A Magyar Pen Club elnöksége táviratban fejezte ki aggodalmát a csehszlovák írószövetségnek V. Havel elítélése miatt - A Magyar Jogász Szövetség intézményes formában kíván segítséget nyújtani az országgyűlési képviselők munkájához Gazdaság: - Országos Tervhivatal Tanácsa a népgazdaság tervezésének megújításáról tárgyalt - A Minisztertanács döntése alapján adókedvezményben részesülnek a gazdaságilag elmaradott térségben üzemeket létesítő gazdaságok